Digital Library for Access to Rare Materials. From pilot projects to national digitisation programmes - Knoll, Adolf (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
More than ten years ago, a first image digitisation product was published by the National Library of the Czech Republic in co-operation with an almost unknown small software company. It was a CD-ROM requested by UNESCO for its Memory of the World programme. After that there were many tests concerning digitisation devices and another two CD-ROM projects were completed to present two interesting manuscripts with rich description metadata related to all the structural levels of the book, including full text. In 1995 - 1996, our first digitisation centre was built to process manuscripts and old printed books. Later, it was upgraded several times with additional devices such as scanners, book cradles for careful document fixation, sophisticated camera stands, microclimate control units, etc. Simultaneously, many software tools were developed to assist the digitisation production. The co-operation with the company became crucial for further development of this activity and both the library and the company grew thanks to each other. In 1999, another project started to output digital data: it was based on the idea of safeguarding acid-paper library materials through preservation microfilming combined with digitisation of microfilm for access purposes. In order to be able to store large amounts of image data produced by this second programme, a mass storage facility was plugged into the digitisation production line. It was based on robotic library using magnetic tapes as storage medium. Successively, the digitisation programmes began to be used also by other Czech institutions holding rare collections of documents: other libraries, museums, archives, and even castle libraries and church institutions. Today, from all the digitised documents almost half of them are from other institutions than the National Library. This is an important success that has taken place thanks to support of the Ministry of Culture through specific grant programmes. Interested institutions can ask the Ministry for up to 70% of the total digitisation cost for their projects with which they apply in calls for proposals.